Analisis Kekuatan Hasil Printer 3D Dengan Filamen Acrylonitrile Butadiene Styrene (ABS) Berdasarkan Variasi Suhu Nosel dan Jenis Isian - Hisyam Ma'mun; Joko Supriyanto; Gostsa Khusnun Naufal; Aan Burhanudin; Rifki Hermana (CV. IRA PUBLISHING, 2025)
Technological advancements, including 3D printing, enable the creation of prototypes from digital designs using 3D printers. A popular method is Fused Deposition Modeling (FDM) with thermoplastic materials such as Acrylonitrile Butadiene Styrene (ABS), valued for its quality and affordability. In 3D printing, nozzle temperature and infill type influence the mechanical properties of printed objects. This study aims to determine the tensile strength of ABS with variations in nozzle temperature and infill type. Tensile test results show that a 230°C nozzle temperature produces higher yield strength for most infill types compared to 240°C. The 240°C setting tends to increase maximum tensile strength for grid and concentric infills, but not for gyroid and lines. The concentric infill type exhibited the highest elongation at both temperatures, indicating greater ductility compared to other infill types. These findings are expected to serve as a reference for optimizing printing parameters.